Особливості розвитку і перебігу пилотоксичних бронхітів у працівників з виробництва алюмінію - Доценко, Сергій Якович; Афанасьєв, Анатолій Віталійович; Данюк, Інна Олександрівна; Тягла, Вікторія Миколаївна; Токаренко, Іван Іванович; Кравченко, Володимир Іванович; Бородавко, Л. І.; Козлова, І. С.; Євтушенко, В. А.; Доценко, С. Я.; Афанасьев, А. В.; Данюк, И. А.; et al. (Чорноморський національний університет ім. Петра Могили, 2018)
В роботі представлено результати вивчення розвитку і перебігу професійних пилотоксичних бронхітів у 70 працівників з виробництва алюмінію (кольорова металургія). Відзначено, що у працівників алюмінієвої галузі пилотоксичні бронхіти розвиваються у відносно молодому віці і при меншому стажі роботи, ніж у працівників чорної металургії і характеризуються більш важким перебігом, що пов'язано зі значно більшою частотою у них розвитку субкомпенсованого легеневого серця, гіпертонічної ішемічної хвороби серця, ураженням венозної системи, кісток, суглобів і шлунково-кишкового тракту, що підтверджено змінами при електрокардіографічному і ехокардіографічному дослідженнях. Зазначені особливості перебігу пилотоксичних бронхітів пояснюються токсичною дією фторидів, які відсутні в чорній металургії. Резюме. В работе представлены результаты изучения развития и течения, профессиональных пылетоксических бронхитов у 70 работников по производству алюминия (цветная металлургия). Отмечено, что у работников алюминиевой отрасли пылетоксические бронхиты развиваются в относительно молодом возрасте и при меньшем стаже работы, чем у работников черной металлургии. Работники цветной металлургии характеризуются более тяжелым течением хронического обструктивного заболевания легких, что связано со значительно большей частотой у них развития субкомпенсированного легочного сердца, гипертонической ишемической болезни сердца, поражением венозной системы, костей, суставов и желудочно-кишечного тракта, что подтверждено изменениями при электрокардиографическом и эхокардиографическом исследованиях. Указанные особенности течения пылетоксических бронхитов объясняются токсическим действием фторидов, которые отсутствуют в черной металлургии. Abstract. Professional chronic obstructive pulmonary disease (COPD) is a topical issue of modern medicine, and occupies to 60% of all occupational diseases. At the same time, the peculiarities of the course of dusttoxic bronchitis in workers of aluminum production are not sufficiently studied. The purpose of the study was to research the clinical features of the appearance, course of dust-toxic bronchitis in workers of aluminum production. Material and methods. We examined 70 workers of aluminum production with COPD (dust-toxic bronchitis) and 70 ferrous metallurgy workers with the same diagnosis. The program of research included objective examination, detection of concomitant diseases, using X-ray of the lungs, spirography, electrocardiography and echocardiography. Results and discussion. Dust-toxic bronchitis developed in workers of aluminum industry at the younger age and with less job tenure than in workers of ferrous metallurgy. Workers of aluminum industry are characterized by more severe course of dust-toxic bronchitis, which is associated with higher incidence of subcompensated pulmonary heart disease and lung hypertension (70%). Workers of aluminum industry are characterized by more significant frequent occurrence of arterial hypertension (48.57%), coronary heart disease (34.28%), thromboembolism of the pulmonary artery (10%), pathology of vein (17.1%), teeth (14.2%), and joints (65.7%). Electrocardiography findings, including tachycardia, bradycardia, extrasystoles, atrial fibrillation, blockades, and hypertrophy of left ventricle were more often diagnosed in aluminum industry stuff (71.4%). Conclusions. Workers of aluminum industry are characterized by more severe course of dust-toxic bronchitis and more frequent occurrence of associated diseases. These particulars of dust-toxic bronchitis course are explained by toxic effect of fluorides, which are absent in ferrous metallurgy. We recommend appointing additional tests to identify the concomitant pathology and adjust treatment for diagnosing and treatment of patients with dust-toxic bronchitis, engaged in the production of aluminum.
Особенности развития и течения пылетоксических бронхитов у работников производства алюминия
Peculiarities of development and course of dust-toxic bronchitis in workers of aluminum production
Keywords: виробництво алюмінію; кольорова і чорна металургія; хронічне обструктивне захворювання легень; пилотоксичні бронхіти; особливості перебігу; производство алюминия; цветная и черная металлургия; хроническое обструктивное заболевание легких; пылетоксические бронхиты; особенности течения; aluminum production; ferrous and non-ferrous metal industry; COPD; dust-toxic bronchitis